Attracting native pollinators : protecting North America's bees and butterflies : the Xerces Society guide - Lee-Mäder, Eric, 1972- (Storey Pub., 2011)
Protect the Pollinators That Help Feed the World: Bees, wasps, butterflies, moths, flies, and some beetles pollinate more than 70 percent of flowering plants, but North America's native pollinators face multiple threats to their health and habitat. The Xerces Society offers a complete action plan of protecting these industrious animals by providing flowering habitat and nesting sites. Providing Healthy Habitats for Pollinators: Supports bountiful farm and garden harvests; Maintains healthy plant communities; Provides food for other wildlife; Beautifies your landscape with flower plants.